Agricultural water development in Sub-Saharan Africa: planning and management to improve the benefits and reduce the environmental and health costs - McCartney, Matthew P.; Boelee, Eline; Cofie, Olufunke O.; Amerasinghe, Felix P.; Mutero, Clifford M. (International Water Management Institute, 2005)
This report analyses environmental and health impacts arising from agricultural water development in Sub-Saharan Africa and recommends ways to increase the sustainability of investments in irrigation by taking into account health and environmental concerns. In many places in the region irrigation is a key means of enhancing productivity that can reduce poverty and improve livelihoods. However, failure to adequately foresee, plan and manage the negative environmental and health impacts arising from irrigation undermines the sustainability of many projects and may worsen poverty. This report is not intended as a compendium of data on environmental and health issues pertaining to agricultural water development. Rather it seeks to provide an overview and framework for understanding policy and programming issues to tackle these issues.